How to use human biomonitoring in chemical risk assessment - Santonen, Tiina (2023)
Funding: This project received funding from the European Union’s Horizon 2020 research and innovation programme under grant agreement No 733032 HBM4EU, and co-funding from the authors’ organisations. The results presented here are based on a huge body of work performed as part of Task 5.3 of the HBM4EU in 2017–2022. First and foremost, we would like to acknowledge all our Task 5.3 colleagues for their valuable contribution to the project work, including the individual RAs and EBoD calculations. In addition, we would like to thank all our other HBM4EU colleagues, the HBM4EU-aligned study data owners, and the other stakeholders who provided support for and feedback on our work during its course.